KEANEKARAGAMAN JENIS TUMBUHAN DI KAWASAN HUTAN KRUI, TAMAN NASIONAL BUKIT BARISAN SELATAN LAMPUNG BARAT - Wardah Wardah (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2005)
Scholaris, ficus deltoidea, and Plants diversity of Krui Dipterocarp forest area and National Park Bukit Barisan Selatan West Lampung have been conducted. Explorative survey methods which including interview and direct field observation was applied in order to collect data of plant usage. A-mong 145 plant species recorded belong to 54 families have been use to in many ways e.q. 63 species for medicinal plants, 32 species for food, 32 species building materials, 3 species for handycraf, and 15 species for others. Four species out of considered endangered species namely Eurycoma longifolia, Alstonia Shorea javanica.